Use of endophytic bacteria from roots of Cyperus rotundus for biocontrol of Meloidogyne incognita - MARDHIANA MARDHIANA; ANKARDIANSYAH PANDU PRADANA; MUH ADIWENA; DWI SANTOSO; RIZZA WIJAYA; ADITYA MURTILAKSONO (Biodiversitas Journal of Biological Diversity, 2017)
Mardhiana, Pradana AP, Adiwena M, Santoso D, Wijaya R, Murtilaksono A. 2017. Use of endophytic bacteria from roots of Cyperus rotundus for biocontrol of Meloidogyne incognita. Biodiversitas 18: 1308-1315. Yield loss due to M. incognita infection in tomato plants cultivation can reach 60%. The problem is able to be solved through the application of endophytic bacteria. In this study, endophytic bacteria from root Cyperus rotundus were isolated using Tryptic Soy Agar media. The bacteria isolates were then tested their safety against plants and mammals. The phenotypic and physiological properties of selected isolates were characterized and tested to know their resistance to antibiotics, and their ability in suppressing the infection rate of M. incognita on tomato. Eighteen bacterial isolates were obtained and 8 of them are categorized as safe bacteria for plants and mammals, which could be used in further tests. A result of the physiological test showed that bacterial isolates were able to produce protease enzyme (87.5%), chitinase enzyme (62.5%), and HCN (37.5%), having urease activity (75%) and could dissolve phosphate (87.5%). Based on the test results, all endophytic bacteria effectively increased tomato growth and suppressed the severity of M. incognita infection with the most stable isolate as a biocontrol agent of M. incognita was CRS16.